2012
DOI: 10.1371/journal.pone.0050953
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Isoforms A and B as well as Insulin Receptor Substrates-1 and -2 Are Differentially Expressed in Prostate Cancer

Abstract: Aims/HypothesisIn different cancers types, insulin receptor isoform composition or insulin receptor substrate (IRS) isoforms are different to healthy tissue. This may be a molecular link to increased cancer risk in diabetes and obesity. Since this is yet unclear for prostate cancer, we investigated IR isoform composition and IRS balance in prostate cancer compared to benign and tumor adjacent benign prostate tissue and brought this into relation to cell proliferation.MethodsWe studied 23 benign prostate sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 26 publications
5
42
0
Order By: Relevance
“…This is consistent with recent work showing that IR-B mRNA is also decreased, without much change in IR-A, in breast cancer tissue (Huang et al, 2011) and supports an emerging concept that maintaining IR-B expression or signaling might limit tumor formation or growth. Selective reductions in IR-B could also explain the enhanced IR-A: IR-B levels found in other cancer tissues Harrington et al, 2012;Heni et al, 2012;Huang et al, 2011;Kalli et al, 2002;Malaguarnera et al, 2011;Sciacca et al, 1999;Vella et al, 2002). In intestinal tumors from Apc Min/+ mice, which represent precancerous adenomas, we observed that Min/+ mice are also consistent with findings in human CRC (Allison et al, 2007;Tricoli et al, 1986;Wong et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is consistent with recent work showing that IR-B mRNA is also decreased, without much change in IR-A, in breast cancer tissue (Huang et al, 2011) and supports an emerging concept that maintaining IR-B expression or signaling might limit tumor formation or growth. Selective reductions in IR-B could also explain the enhanced IR-A: IR-B levels found in other cancer tissues Harrington et al, 2012;Heni et al, 2012;Huang et al, 2011;Kalli et al, 2002;Malaguarnera et al, 2011;Sciacca et al, 1999;Vella et al, 2002). In intestinal tumors from Apc Min/+ mice, which represent precancerous adenomas, we observed that Min/+ mice are also consistent with findings in human CRC (Allison et al, 2007;Tricoli et al, 1986;Wong et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have also reported elevation of IR-A expression in various cancers; therefore, studies on the IR isoforms in cancer cells have primarily focused on IR-A Frittitta et al, 1999;Harrington et al, 2012;Heni et al, 2012;Huang et al, 2011;Malaguarnera et al, 2011;Sciacca et al, 1999;Vella et al, 2002). Here, we provide novel evidence for loss of IR-B in spontaneous small intestinal and colon adenomas in Apc Min/+ mice, and in aggressively growing, poorly differentiated human CRC cell lines.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, hyperinsulinaemia may exert mitogenic effects mediated through the IGF1R, but as it was recently demonstrated in mice in vivo using the mitogenic insulin analogue AspB10, the mitogenic effects can also be exerted through the IR itself. 190 In parallel, it was also shown in previous in vitro studies that the IR, predominantly the more mitogenic IR-A isoform, is overexpressed in many types of cancer, [191][192][193][194][195] and insulin as well as insulin analogues appears to be able to stimulate the growth of various tumour cells in vitro through IR-A, although the existing data revealed some heterogeneity. [196][197][198][199] Here, we will focus on insulin analogues in humans trying to clarify the safety concerns raised by the in vitro studies.…”
Section: Insulin-based Therapies and Cancer Riskmentioning
confidence: 78%
“…Our laboratory has previously published data on the findings of increased INSR expression in prostate cancer cells, with validation in LNCaP xenografts using murine CRPC models [100,101]. We demonstrated progressive increase in expression of INSR in prostate cancer cells with increasing duration of neoadjuvant hormone therapy and CRPC cells, the level of expression which could be correlated with biochemical progression to CRPC [4].…”
Section: Rationalementioning
confidence: 98%
“…Mutations in downstream pathways of the insulin receptor are well documented in CRPC and high-grade tumours [4,100,101], such as the PI3K signalling pathway, commonly associated with a loss of the negative regulator PTEN [65]. Recent research has also revealed various survival mechanisms that are thought to be initiated by insulin.…”
mentioning
confidence: 99%